Penggunaan Media Pop Up Book terhadap Meaningful Learning pada Pembelajaran IPS Materi Keragaman Budaya Kelas IV Sekolah Dasar - Nadiya Andhini; Mintasih Indriayu (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2026)
This study aims to explore the relationship between the implementation of pop-up book media in cultural diversity materials and the meaningful learning process experienced by students. This article employs a literature study approach by reviewing several previous studies summarized in a citation table to identify patterns of findings and the contribution of pop-up book media to the learning process. Data were collected from various scientific journal sources and then analyzed using a descriptive qualitative method to obtain a comprehensive understanding. The findings indicate that pop-up book media, which is visual, concrete, and collaborative in nature, can encourage student engagement, facilitate conceptual understanding, and connect new information with prior knowledge. This condition is in line with the theory of meaningful learning, which emphasizes the importance of integrating new information into students’ cognitive structures and active involvement during the learning process. The use of pop-up book media in cultural diversity materials has been proven to support the creation of more meaningful learning, enhance students’ understanding, and foster an attitude of appreciating cultural diversity in daily life.